Domestication of Ganoderma Leucocontextum, G. Resinaceum, and G. Gibbosum Collected from Yunnan Province, China - Luangharn, T.; Mortimer, P.E.; Karunarathna, Samantha C; Hyde, Kevin D.; Xu, J.C. (Oriental Scientific Publishing Company, 2020)
Ganoderma mushrooms have been used in traditional medicines for centuries and as such are highly sought after, especially in Asia. The present study is the first report of the successful cultivation of G. leucocontextum, G. resinaceum, and G. gibbosum collected from the wild, in Yunnan Province, China. One mature fruiting body of the laccate G. leucocontextum, one mature fruiting body of the laccate G. resinaceum, and seven non-laccate G. gibbosum fruiting bodies were collected and isolated into culture. These strains were cultivated using both soil casing layer and non-casing layer methods. The highest yield and biological efficiency (BE) of G. leucocontextum was obtained when using the soil casing layer method (60.43% BE, with 253.82 g/Kg-1 of the total yield) with the non-casing layer method (13.60% BE, with 58.18 g/Kg-1 of the total yield), respectively. Only one cycle of production (26.94% BE and 7.02 g/Kg-1) was obtained for G. resinaceum KUMCC19-0001 when the soil casing layer method was applied, while a high yield of 109.26% BE, with a total yield of 27.75 g/Kg-1, was obtained when the non-casing layer method was used. A BE of 73.80% and total yield of 284.15 g/Kg-1 were obtained for the G. gibbosum KUMCC17-0005 when it was cultivated with a soil casing layer, while a BE of 40.26% and a total yield of 172.08 g/Kg-1 was obtained when the non-casing layer method was used. Based on this comprehensive study, this result will be helpful for the commercial cultivation for laccate G. leucocontextum, G. resinaceum, and non-laccate G. gibbosum.